An assessment of self-driving vehicles: road maintenance and infrastructure needs - Kondratovič, Vladislav; Čygas, Donatas; Palevičius, Vytautas (International Conference “Environmental Engineering”, 2023)
In the coming years, on the roads of the European Union countries, we will increasingly see self-driving vehicles (SDV), which will face considerable challenges on the roads. At first, SDVs will aim to adapt to the existing road infrastructure, but their increasing use on roads will make tangible influence on the progress of the components of the road infrastructure ecosystem. The following main trends in global car transport can be distinguished: artificial intelligence in SDV, various SDV digital and communication systems, SDV sharing platforms and other components of the SDV ecosystem. Although the benefits of using new autonomous technologies for transport have been widely explored, research on requirements for the physical infrastructure for the SDV traffic is still at an early stage. In this context, the emergence of new technologies calls for immediate action to adapt the existing transport infrastructure system to the evolving SDV industry. This paper examines the impact of SDVs on the physical road infrastructure in order to identify road infrastructure elements that influence the SDV traffic.